Black Parade: Conceptualizing Black Adolescent Girls' Multimodal Renderings as Parades. (December 2022) - Griffin, Autumn A.
This piece builds on scholarship in African American parading and Black Girls' Literacies by presenting parading as a metaphor to analyze a website created by nine Black adolescent girls. I draw on multimodal analysis frameworks to understand the symbolic nature of the site and its components, as well as how the girls use it as a platform to speak to issues of racism, sexism, self-definition, joy, and celebration. The girls write against liminal perceptions of their identities, (re)positioning themselves and their lives as worthy of celebration and themselves as experts of Black girlhood.